Le nécrophile, pervers insaisissable (France, XIXe siècle) - Amandine Malivin (Criminocorpus)
During the summer of 1849, the Paris Council of War sentences François Bertrand, "the Vampire of Montparnasse", to one year in prison for violating graves. The extraordinary case of this young soldier visiting cemeteries in the middle of the night to exhume, mutilate and perform sexual acts on dead bodies quickly gets the attention of the medical doctors. This inaugural case becomes the basis of necrophilia discourses, and Bertrand the model of a new perverse figure. In the following decades, several other cases come to light. Still, confronted to this extraordinary transgression, lawmen and medical doctors alike are hard pressed to find a place for these deviant individuals in the legal and scientific doctrines, therefore contributing to the perpetuation of a fantasized figure of transgression, disconnected from the real subjects.